Thermophotovoltaic systems for achieving high-solar-fraction hybrid solar-biomass power generation. (1st February 2020) - Hussain, C.M. Iftekhar; Duffy, Aidan; Norton, Brian
Highlights: A new concept for hybrid solar-biomass thermophotovoltaic is implemented in TRNSYS simulation environment. TPV algorithm is developed and analysed to compare and validate with related previous work. Validated TPV algorithm is simulated for two system configurations to evaluate their output parameters. Results show; a TPV system could recover surplus thermal energy gained from CSP power plant at mid-days. Abstract: Medium operating temperature hybrid solar-biomass TPV power plant design requires complex integration of multiple high temperature processes with low band-gap TPV cells. A 0.72 eV band-gap GaSb TPV cell has been used in thermophotovoltaic (TPV) systems operating at temperatures above 1400 °C. Low band-gap TPV cells, such as InGaAs (Eg  = 0.55 eV) and InAs (Eg  = 0.36 eV) could enable a TPV system to operate optimally at temperatures ≈1000 °C. To examine this, two hybrid solar-biomass TPV system configurations are studied using TRNSYS simulation that incorporates a new algorithm for TPV. It is found that in a high solar fraction CSP power plant, a TPV system could recover surplus thermal energy gained from solar energy at mid-days that would otherwise be unused.